Development of a comprehensive economic enterprise development program in the Philippines - Armas, Kenneth Lucto; Moralde, Rachael Reyes (Asian Development Policy Review, 2023)
This study aims to design a sustainable and comprehensive economic enterprise development program for communities in Cabanatuan City through an asset-based community development (ABCD) approach. The concept consists of two phases: capacity building and company development. Community capacity building focuses on enabling all community members to acquire the skills and competencies they need to take more responsibility for their own lives and contribute to inclusive local development. The key components of the capacity development phase are community planning, community organization, community need assessment, gap analysis, project programming, project execution, project monitoring, and evaluation. Community planning involves choosing the most viable community business ventures based on six economic factors: market, capital, raw materials, service providers, support infrastructure, and appropriate technology. Enterprise development is a low-cost, straightforward training strategy for aiding entrepreneurs and microbusiness owners with business planning and expansion. This component is further subdivided into enterprise growth, local government assistance, developing industry connections, enterprise marketing and promotion, enterprise performance monitoring and evaluation, and impact assessment. Acquiring economic aptitude is essential for the survival of Cabanatuan City's citizens and provides them with a sense of self-worth and communal pride.